KELIMPAHAN KEPITING BAKAU (Scylla sp.) DI TAMAN WISATA MANGROVE PANDAN ALAS, DESA SRIMINOSARI, LAMPUNG TIMUR - Fandi Baharuddin; Henni Wijayanti; Nidya Kartini (Fakultas Perikanan dan Ilmu Kelautan, 2023)
Mangrove crabs (Scylla sp.) are related to the surrounding ecosystem, especially in the mangrove ecosystem. The purpose of this study is to identify the species of mangrove crabs (Scylla sp.) found in the Pandan Alas Mangrove Tourism Park, Sriminosari Village, East Lampung, and examine the relationship between the abundance of the crab and environmental parameters. This research was conducted in October-November 2022 at the Pandan Alas Mangrove Tourism Park, East Lampung. Data analysis used was PCA (Principal Component Analysis). Mud crabs found in the Pandan Alas Mangrove Tourism Park was Scylla serrata and Scylla olivacea. Based on PCA results, parameter which affect mangroves crab abundance in Pandan Alas Mangrove Tourism Park was BOT (Total Organic Matter), substrate, and soil pH.